2019
DOI: 10.1097/mph.0000000000001690
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of Invasive Fungal Diseases (IFD) of the Central Nervous System in Children With Lymphoid Malignancies

Abstract: Background: Outcomes of childhood hematolymphoid malignancies have improved several fold because of immunosuppressive chemotherapy and broad-spectrum antibiotics for managing febrile neutropenia. An apparent trade-off has been an increase in invasive fungal disease (IFD), affecting multiple organs. We report the diagnostic and therapeutic challenges in 8 children with lymphoid cancers who developed intracranial (IC) fungal abscesses between 2010 and 2017. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Patients with acute myeloid leukemia are more prone to fungal infections. However, as more than 80% of all leukemias detected in childhood are acute lymphoblastic leukemia (ALL), and CNSFI occurs mostly in ALL cases as in our study15 and mostly during induction treatment 16. Candoni et al12 reported that CNSFI was more common in patients with ALL and in relapsed/refractory patients, 74% of the patients were neutropenic.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Patients with acute myeloid leukemia are more prone to fungal infections. However, as more than 80% of all leukemias detected in childhood are acute lymphoblastic leukemia (ALL), and CNSFI occurs mostly in ALL cases as in our study15 and mostly during induction treatment 16. Candoni et al12 reported that CNSFI was more common in patients with ALL and in relapsed/refractory patients, 74% of the patients were neutropenic.…”
Section: Discussionsupporting
confidence: 52%
“…However, as more than 80% of all leukemias detected in childhood are acute lymphoblastic leukemia (ALL), and CNSFI occurs mostly in ALL cases as in our study 15 and mostly during induction treatment. 16 Candoni et al 12 reported that CNSFI was more common in patients with ALL and in relapsed/ refractory patients, 74% of the patients were neutropenic. In our study, most episodes (66%) occurred during the early intensification phase of the BFM ALL protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnostic images provide an additional benefit in opportune surgical planning, evaluating orbital and central nervous system extension. Ruling out intracranial extension is critical as it is associated with a high mortality rate of 75%–100% despite radical surgery and antifungal therapy ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral IFI can be treated by TDM-guided azole dosing and surgical intervention and may yield improvement in some cases. 86…”
Section: Pharmacokineticsmentioning
confidence: 99%